(untitled) (The Peerian Journal, 2023)
This paper presents the synthesis and identification of (1,3-dioxoisoindolin-2- yl)methyl phosphoric acid and the corrosion rate and protection levels of the DIIMFK inhibitor Fon-1 in solution at various temperatures and concentrations